Reading, Mind Mapping, Sharing (RMS) And Reading, Questioning, Answering (RQA): Their Effect On The Higher-Order Thinking Skills (HOTS) - Rizhal Hendi Ristanto; Rusdi Rusdi; Maghfirah Idzati Aulia (Universitas Tidar, 2023)
The respiratory system is one of the topics in Biology that requires students’ Higher Order Thinking Skills (HOTS). In the respiratory system learning, teachers can implement constructivism-oriented learning models, such as Reading, Mind Mapping, Sharing (RMS) and Reading, Questioning, Answering (RQA). This study aims to measure students’ HOTS and analyze differences in the implementation of RMS and RQA learning models for students’ HOTS in the respiratory system topic. The research method is a quasi-experiment with pretest-posttest control group design as the research design. The research employs two experimental classes for the RMS and RQA model and one control class. The research population is the SMAN students in DKI Jakarta Province. The research sample consists of 81 students selected using a multistage sampling. The percentage results of HOTS categorization indicate an improvement in the percentage of students in the high HOTS category in each class. The hypothetical testing conducted using One Way Inova at α=0.05 gains a significance value of 0.139. The research results suggest no significant differences between RMS and RMQ learning models for HOTS in the respiratory system topic.